Impact of rain and soiling on potential induced degradation. (16th May 2016) - Koehl, Michael; Hoffmann, Stephan
Abstract: The electrical potential between the cells and ground can cause leakage currents that are a necessary but not sufficient indicator for potential induced degradation that is because of the migration of sodium ions into the silicon cells. Outdoor exposure of modules with high‐voltage bias in two different climate regions with monitoring of the climatic data, the module temperatures as well as the leakage currents was used to investigate the effect of rain‐induced and soiling‐induced increase of the surface conductivity, the leakage current and the decrease of the module performance.